Proces nawrócenia się Abrahama w interpretacji Filona z Aleksandrii - Wyrzykowski, Mateusz (Warszawskie Studia Teologiczne, 2023)
The article aims to present a reinterpretation of the history of Abraham's calling in the treatise of Philo of Alexandria. The text of Genesis (12:1-4) describes the patriarch's immediate reaction to the command to leave Haran. This process began in Ur. According to Philo, building a relationship between God and Abraham required proper preparation. First, he gave up worshiping the gods, and then he discovered that the world is material and spiritual. Philo emphasizes the long-term nature of the conversion process. This article presents and explains its individual stages - not described in the Hebrew Bible.